A Study on Psychodinamic of the User of Ecstasy - Sardinha, Luís Sérgio (2000)
The present paper has as objective to do an initial study on aspects of the user's of Ecstasy psychodinamic, trying to understand which the meaning of this drug in the individual's life inserted in a historical context of powder-modernity. He/she/you broke of studies already accomplished on users of other drugs and historical abbreviation on Ecstasy, later he/she took place interviews semi-driven that were analyzed later. The difficulty in the collection of data demonstrates that the users difficulty talk openly about the subject when they are not in treatment. Starting from the analysis of the accomplished interviews it can be noticed that the drug is still consumed occasionally. It was also noticed that the alienated man of the great center urban search other integration forms, making possible a removal of the reality and a refuge in an own world.